Degradação de levofloxacino e imidacloprido: um estudo da geração de radicais catalisada por resíduo da siderurgia - Nascimento, Carlos Pedro Gonçalves do (2023)
In this work, the use of mill scale, a steel waste formed in the continuous casting stage of steel production, was evaluated as an activator of hydrogen peroxide (H2O2) and peroxymonosulfate (PMS) to promote the generation of reactive oxygen species (ROS) through Fenton-like reactions, without the need for any external energy sources, which makes the process less costly. The efficiency of the residue in these reactions is related to its high iron content, which was quantified by flame atomic absorption spectroscopy, presenting around 42% by mass of the metal. This high iron content can be explained by the majority presence of iron oxides, such as wustite (FeO), hematite (Fe2O3) and magnetite (Fe3O4), all identified by X-ray diffraction and confirmed by Mössbauer spectroscopy. The reactive species generated were able to promote the degradation of two organic contaminants in aqueous solution: the drug levofloxacin (LVF), as well as the insecticide imidacloprid (IMD), in addition to leading to the mineralization of part of what was degraded from these compounds in aqueous solution. After 1 hour of reaction, the H2O2/mill scale system promoted a degradation of 93% of LVF and the mineralization of about 70% of the compound, while the degradation of IMD was 80% after 2 hours, and practically all of this percentage underwent mineralization. Reactive species capture tests indicated that the hydroxyl radical (HO•) was responsible for the degradation of the insecticide in the H2O2/mill scale system, while in the degradation of LVF, although this radical was the most active species, the superoxide/hydroperoxyl radicals (O2•-/HO2•) also participated in the decomposition of the drug in the studied system. Through the tests using the filtrate of the heterogeneous system solution, obtained after the reaction in the H2O2/mill scale system, it was possible to evaluate the contribution of the homogeneous reactions on the degradation of both compounds in the Fenton-like heterogeneous system. The results indicated that the degradation of LVF occurred mainly through homogeneous reactions, propitiated by the leaching of iron ions in the H2O2/mill scale system, while the degradation of IMD was predominantly favored by surface reactions. In addition, the mill scale showed high stability against iron ion leaching, with rates around 3.3–4.4 mg of iron per gram of scale after degradation of LVF, and approximately 1.3 mg per gram of scale after IMD degradation, which represents only about 1.0% and 0.3% of the total metal content released after LVF and IMD degradation, respectively. X-ray analyzes of the residue after the IMD degradation reaction indicated that the iron content released from the material was mainly from the hematite phase (Fe2O3). In addition, excellent reuse capacity was received by the mill scale, maintaining the same drug degradation rates in up to 5 verified reaction cycles, and losing only around 15% efficiency in insecticide degradation throughout the 5 reaction cycles.